RESOURCE-BASED VIEW: STRATEGI UMKM DI SUMATERA BARAT UNTUK MENCAPAI KEUNGGULAN KOMPETITIF - Hesty Aisyah; Sari Puspita; Elizamiharti Elizamiharti (STIE PGRI Dewantara Jombang, 2022)
West Sumatra has a number of MSMEs that tend to increase every year. However, these MSMEs are still lacking confidence because of the limitations they have, such as difficulties in funding, lack of technological tools to support operational activities, and lack of knowledge in the scope of business strategy. This research is a type of empirical research in the form of a literature study originating from five previous studies. The keywords used in the selection of articles were: 1) 2019-2020 criteria, 2) discussing MSMEs, 3) using the Resource-Based View (RBV) strategy, 4) using the VRIO theory (valuable, rare, inimitable, organization). From the research results, it was found that RBV with VRIO analysis contributed positively to MSMEs in gaining competitive advantage. Valuable, rare, imitability and organization are internal assets or resources owned by tangible and intangible MSMEs. VRIO optimally contributes to competitive advantage if applied together to strengthen one another.